Determinants of Malnutrition in Older Adults in Indonesia: A Literatur Review - Rini Ismiyati; Sitti Nur Djannah; Sunarti Sunarti (Universitas Ibn Khaldun Bogor, 2026)
Malnutrition in older adults is an increasingly important public health issue, particularly as the proportion of the elderly population in Indonesia continues to rise. This condition is driven by a complex interplay of physiological, psychological, social, and economic factors that contribute to nutritional imbalance. This study aims to identify and analyze the determinants of malnutrition among older adults in Indonesia through a systematic review of relevant observational studies. A literature review was conducted using the PIOT framework to guide the search strategy. Data were retrieved from three major databases (Google Scholar, PubMed, and ScienceDirect) using specific keywords in both Indonesian and English. Included articles were published between 2020 and 2025 and met inclusion criteria based on relevance, study design, and full-text accessibility. Of the 25,593 articles screened, 10 studies met the inclusion criteria. The findings indicate that malnutrition among older adults in Indonesia is influenced by various factors, including chronic diseases, depression, cognitive decline, advanced age, low levels of education and income, dependence in daily activities, inadequate intake of energy and micronutrients, and limited social and family support. Malnutrition in older adults is a multifactorial condition requiring a holistic and multidisciplinary intervention approach. Prevention and management strategies should involve family support, nutrition education, promotion of functional independence, and improved access to healthcare services and nutritious food.